Study and design of MIMO antennas for ITS applications - Yang, Fengyuan (2016)
The multiple-input multiple-output (MIMO) antenna technology is an emerging and promising technology for wireless communications in Intelligent Transportation System (ITS) applications. This project is for studying concepts of MIMO antennas and designing an appropriate MIMO antenna for ITS applications. First, varieties of antennas are analyzed to better understand antennas and prepare for the MIMO antenna design. Study of antennas begins with basic dipole and monopole antennas, then inverted-F antennas, and phased array antennas, ends with uniform circular array antennas. The final optimized design is a 7-element antenna, with one center reflector and six monopoles in uniform circular array. This 7-element antenna design has a higher gain than the 17-element antenna analyzed in literature. Then phase analysis is conducted to realize the MIMO application. Besides, theories of MIMO are studied to better understand concepts of MIMO system. Moreover, application and testing of MIMO antenna is discussed to complete the background knowledge as well as for further research. In the designed 7-element antenna, every time two ports are activated together to form a directional radiation pattern. By altering their phase difference, within the field of view (FOV) of 60˚, a gain exceeding 4.5dB can be achieved, and within the FOV of 120˚, a gain above 3.7dB can be obtained. Hence, all the six monopoles can cover a direction of 360˚ with high gains compared with 0.3dB gain of a single reference monopole. Therefore, the designed antenna is suitable for the desired MIMO system in ITS applications.